The Combination of Scramble Word Game and Make a Match Method in Teaching Narrative Text on Reading Comprehension - Juria Ulfah Rumodar (TEKILA: Journal of Language Teaching and Literature, 2025)
This study aimed to investigate the effect of the Scramble Word Game combined with the Make a Match method on students’ reading comprehension. Reading comprehension remains a challenging skill for many EFL learners, particularly at the junior high school level, where students often struggle to understand texts due to limited vocabulary and low learning motivation. To address this issue, this study employed a pre-experimental research design using a one-group pre-test and post-test approach. The participants of the study were 24 eighth-grade students at a junior high school. Data were collected through a reading comprehension test administered before and after the implementation of the Scramble Word Game and Make a Match method. The treatment was conducted over several instructional sessions, in which students actively participated in game-based reading activities designed to improve vocabulary recognition, text understanding, and learner engagement. The collected data were analyzed using a paired sample t-test to determine whether there was a statistically significant difference between students’ pre-test and post-test scores. The findings revealed a significant improvement in students’ reading comprehension after the treatment. The post-test mean score was higher than the pre-test mean score, indicating that the combined use of the Scramble Word Game and Make a Match method had a positive effect on students’ reading comprehension. These results suggest that interactive and collaborative learning activities can enhance students’ motivation, participation, and understanding of reading texts. This study highlights the pedagogical value of integrating game-based learning strategies into English reading instruction and provides practical implications for EFL teachers seeking to create a more engaging and effective learning environment.